PEMERIKSAAN BAKTERI COLIFORM PADA SAMPEL DEPOT AIR MINUM ISI ULANG (DAMIU) - Teguh Azizah; Indah Sulistiyawati (Bioscientiae, 2026)
Water is one of the basic human needs, because humans are very dependent on air for both drinking and daily life. Air quality that includes is very important to ensure safe drinking water, but it is also important to consider the broader impacts of air management practices. Refill Drinking Water Depot (DAMIU). This study aims to ensure that drinking water is safe and suitable for consumption. This study was to examine coliform bacteria in drinking water samples from Refill Drinking Water Depot (DAMIU) using the membrane filter method, with 10 samples. This study uses the Membrane filter method, which is a technique used to test water samples to identify the presence of coliform bacteria and Escherichia coli. The results of testing 10 drinking water samples can be concluded that some of the quality of drinking water at the research location is still different and has not fully met the quality standards. The results are not in accordance with the maximum limit of coliform and E. coli in drinking water is 0 CFU / 100 mL in the drinking water quality standards set by the Regulation of the Minister of Health of the Republic of Indonesia (PERMENKES) Number 2 of 2023. The influencing factors are raw materials, length of time the water is stored in the reservoir, handling of the buyer's container, operator cleanliness, and environmental cleanliness around the DAMIU which is less noticed.